E-Marketing Summerfashion.bali - Kadek Artika Adelina; I Gusti Made Dharma Hartawan (Jurnal Publikasi Ekonomi dan Akuntansi, 2022)
The results of this study show that E-Marketing has many benefits, such as reaching more people compared to opening an offline store. Its reach is more throughout Indonesia and even abroad. The author's suggestion is to increase the idea or innovation of various types of products according to consumer trends and desires so that they can provide many choices and attract consumers to buy at the Summerfashion.bali store. and to further increase product stock so that consumers get the products they want.